New clinical scoring system for prognosis of early recurrence of colorectal liver metastases after surgical treatment - Alan, Sutnar; Vaclav, Liska; Martin, Pesta; Vladislav, Treska; Ondrej, Topolcan; Tomas, Skalicky; Stanislav, Kormunda; Lubos, Holubec (Hepato-gastroenterology, 2011)
BACKGROUND/AIMS: To determine the relationship between the mRNA expression of MMP-2, MMP-9, TIMP-1, TIMP-2 and CEA in tumour tissue and preoperative serum levels of these tumour markers in patients with colorectal liver metastases (CLM). Additionally, to establish a new scoring system based upon these results in combination with the volume of the metastatic process to identify patients with a high risk of early recurrence of CLM. METHODOLOGY: The correlation between the mRNA expression of CEA, TIMP-1, TIMP-2, MMP-2 and MMP-9 in tissue samples and preoperative serum levels of the named tumour markers was performed on 27 patients. The scoring system was proposed as a combination of all the independent parameters (mRNA expression of TIMP-1, MMP-9 and CEA in tumour tissue samples and preoperative serum levels of CEA and TIMP-1) in combination with the volume of the metastatic process. The evaluation was conducted in relation to the disease free interval (DFI). RESULTS: We observed a statistically significant relationship between the volume of liver metastases and DFI (p<0.0337). The scoring system divided the patients into groups with a tendency of early recurrence (p<0.0126). CONCLUSIONS: The high stages in our scoring systems augment the risk of recurrence. The proposed scoring system was shown to be an efficient instrument helpful in complex surgical and oncological access to patients after radical surgical treatment of CLM.
Keywords: dospělí; kolorektální nádory; Recurrence; matrixová metaloproteinasa 2; karcinoembryonální antigen; Carcinoembryonic Antigen; tkáňový inhibitor metaloproteinasy 2; Adult; Colorectal Neoplasms; lidé; nádory jater; recidiva; messenger RNA; Aged, 80 and over; Matrix Metalloproteinase 9; prognóza; RNA, Messenger; tkáňový inhibitor metaloproteinasy 1; Tissue Inhibitor of Metalloproteinase-2; Liver Neoplasms; Tissue Inhibitor of Metalloproteinase-1; matrixová metaloproteinasa 9; Aged; Prognosis; lidé středního věku; senioři nad 80 let; senioři; Matrix Metalloproteinase 2; Middle Aged; Humans